2020
DOI: 10.29245/2578-2959/2020/2.1198
|View full text |Cite
|
Sign up to set email alerts
|

Personality Profiles of Individuals with Substance Use Disorders: Historical Overview and Current Directions

Abstract: Efforts to understand personality features of people who use psychoactive substances have a long history, dating back to early psychoanalytic conceptualizations. Advancements in the field have focused on applying multidimensional personality inventories to better understand personality differences between substance users and non-users, and between different substance use types, with respect to both psychopathological traits and broad dimensional factors. A brief review of this evidence highlights personality f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Heavy substance use (SU) and substance use disorders (SUD) are highly prevalent conditions that can have severe consequences for individuals, their families, and society (Gowing et al, 2015). According to vulnerability/diathesis-stress-models (Whelan et al, 2014;Wittchen et al, 2014;Zuckerman, 2000), SU(D) results from interactions between environmental stressors, psychosocial characteristics, and individual vulnerabilities, including specific personality traits (Kotov, Gamez, Schmidt, & Watson, 2010;Nevid, Gordon, Miele, & Keating, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heavy substance use (SU) and substance use disorders (SUD) are highly prevalent conditions that can have severe consequences for individuals, their families, and society (Gowing et al, 2015). According to vulnerability/diathesis-stress-models (Whelan et al, 2014;Wittchen et al, 2014;Zuckerman, 2000), SU(D) results from interactions between environmental stressors, psychosocial characteristics, and individual vulnerabilities, including specific personality traits (Kotov, Gamez, Schmidt, & Watson, 2010;Nevid, Gordon, Miele, & Keating, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The predictive role of personality traits in SUD has been widely studied (for a meta-analysis see Kotov et al, 2010). In line with the vulnerability model, numerous studies have shown that certain trait levels, especially high neuroticism, impulsivity, and sensation seeking, as well as low self-directedness and harm avoidance, relate to an increased risk for SUD (Dash et al, 2019;Kotov et al, 2010;Nevid et al, 2020;Sher, Bartholow, & Wood, 2000;Whiteside & Lynam, 2009). In contrast, much less is known about personality changes associated with SU(D) (Blonigen et al, 2015;Kroencke, Kuper, Bleidorn, & Denissen, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the very few similar studies from African countries, a Nigerian study that reported low agreeableness trait and high extraversion trait scores as significantly associated with lifetime alcohol use among undergraduate students [9]. Research [10][11][12][13][14][15][16] has additionally shown that certain personality profiles are somewhat predisposed to using substances (generally high neuroticism, high openness to experience, low agreeableness, and low conscientiousness) or even linked to a preferential choice of drug. To date, there has been no local systematic study to validate these findings, yet they are often cited as having universal application.…”
Section: Introductionmentioning
confidence: 99%
“…However, research on the FFM with children is also flourishing, demonstrating that personality traits predict school performance and intelligence [ 57 , 58 , 59 ], self-esteem [ 57 ], and measures of internalizing and externalizing disorders [ 57 , 60 , 61 ] in middle childhood and adolescence. Other studies on adolescents have analyzed the predictive role of personality traits for substance addiction such as drugs [ 62 ], but studies related to behavioral addiction adopted mainly a correlational design approach in studying the linear associations between personality traits defined in line with the FFM and Internet addiction [ 63 ], gaming addiction [ 64 ], or social networking addiction [ 65 ]. The current study aims to overlap this gap, starting from the consideration that the underlaying structure of personality for behavior, even if measured and empirically evaluated in adults, may be a feature of significant novelty and relevance, both to research and to the preventive policy of addictive behaviors, since the earliest ages.…”
Section: Introductionmentioning
confidence: 99%